Report of 24th General assembly - ASEAN Inter-parliamentary organization - Asean Inter- parliamentary assembly, Hội đồng liên nghị viện ASEAN (ASEAN Inter - Parliamentary Assembly (AIPA), 2003)
Hội nghị lần thứ 24 của tổ chức liên nghị viện ASEAN được tổ chức tại Jakarta, Indonesia từ ngày 7-12 tháng 9 năm 2003.